Differential diagnosis in patients with suspected bile acid synthesis defects - Haas, Dorothea; Gan-Schreier, Hongying; Langhans, Claus-Dieter; Engelmann, Guido; Hoffmann, Georg F.; Okun, Jürgen G. (World journal of gastroenterology, 2012)
Differential diagnosis in patients with suspected bile acid synthesis defects